Painting Systems: From Art to Systems Architecting. Issue 1 (13th September 2016) - Salado, Alejandro; Iandoli, Luca; Zollo, Giuseppe
Abstract: Systems engineering has successfully contributed to develop complex systems in industries such as defense, space, energy, or transportation. Systems in those industries have in common their engineered or socio‐technical natures. However, systems engineering has been understood for a long time as both an art and a science. As a matter of fact, principles and practices of systems engineering have been exhibited in the creation of film original score, a major artistic endeavor. Therefore, it is sensible to investigate if and how the similarities and differences between the application of systems engineering in the development of engineered systems and the pursue of artistic endeavors can help in improving the understanding and practice in both domains. Specifically, this paper discusses how the same concepts are applied in artistic painting and in system architecture to reduce complexity and achieve elegance.